Which is the optimal exercise to strengthen supraspinatus? - Boettcher, C. E.; Ginn, K. A.; Cathers, I. (Medicine & Science in Sports & Exercise, 2009)
Purpose: Supraspinatus strengthening is an important part of shoulder rehabilitation programs. Because of the force-couple relationship between supraspinatus and deltoid during shoulder abduction, it has been proposed that the optimal exercise to strengthen supraspinatus is one that would maximize supraspinatus activity while minimizing surrounding muscle activity, particularly deltoid. The aim of this study was to simultaneously examine all exercises known to recruit supraspinatus at high levels and to compare the level of recruitment in supraspinatus, deltoid, and infraspinatus.